Dedication of Justice George A. Hopper Room at Fresno County Law Library - Watkins, Howard::::::::: (1982)
Justice Hopper's son George Hopper, Jr., Dorothy Morris, framed photograph of Justice George Hopper, Grace Hopper, Judge Annette LaRue